Effective Strategies to Strengthen Religious Moderation in Schools Based on the Perspective of Christian Ethics - Waruwu, Anwar Three Millenium (Jurnal Apokalupsis, 2023)
The increasing level of intolerance within the upper secondary education environment across five cities in Indonesia has emerged as a crucial issue, highlighting the urgent need for strengthening religious moderation. This article focuses on the problem of an inability to appreciate religious diversity and the readiness of students to defend their faith even to the extent of sacrificing lives. The emphasis lies in examining the influence of parents, the role of religious instructors, social surroundings, extracurricular organizations, and religious literature in shaping a perspective of tolerance. The research methodology employs a qualitative approach involving literature review, analysis of Biblical texts, and a comprehensive review of previous studies. Findings indicate that the Christian Ethics perspective forms a robust foundation for reinforcing religious moderation. Concrete strategies encompass regular consultations with parents, the role of instructors in inclusive education, extracurricular organization involvement, and the utilization of religious literature. Implementing evidence-based strategies with periodic evaluations is pivotal in ensuring sustained positive impacts within the educational setting. Overall, this article asserts that the Christian Ethics perspective provides a strong basis for promoting tolerance, interfaith cooperation, and appreciation of religious diversity in the pursuit of religious moderation within the educational environment.